Implementing E-Learning on arabic Language Subject During Covid 19 Pandemic in Madrasah Aliyah Negeri 1 Boalemo - Mukhtar I Miolo; Sinta Djafar; Damhuri Damhuri; Ratni Bt. Hj. Bahri (Universitas Muhammadiyah Gorontalo, 2022)
The purpose of this study was to describe (1) the implementation of e-learning in Arabic subjects at MAN 1 Boalemo, (2) Supporting and Inhibiting Factors in the implementation of e-learning in Arabic subjects at MAN 1 Boalemo. The type of research used is descriptive qualitative. Methods of data collection using observation, interviews and documentation. The data analysis techniques used are data collection, data reduction, data presentation and conclusion drawing. The informants in this study were 24 people consisting of four teachers, namely the Principal, Arabic Subject Teacher, Web-E-Learning Manager, Class Teacher and 20 class XI students.The results of this study indicate that the implementation of e-learning in Arabic subjects during the Covid-19 pandemic at MAN 1 Boalemo is very good and complete because all forms of questions in the form of images, videos, and sounds can be done through e-learning and as for features in e-learning consists of the homepage, absences, announcements, messages, teaching schedules, assignments, materials, achievement of basic competencies, group assignments, teacher filters, student filters and logout or exit. The implementation of e-learning is carried out in three stages, starting from (1) the preparation stage where teachers and students attend training on how to use e-learning so that at this stage students and teachers are more demanded to be able to use information and communication technology in the form of e-media. -learning. (2) the implementation stage, at this stage the e-learning learning during the covid 19 pandemic carried out by the Arabic language teacher was more to provide material in the form of videos or voice notes then work on Arabic language questions so that at this stage students are required to learn independent and easier for students to access material anytime and anywhere. (3) Evaluation Stage. At this stage, what is done is more about the results of learning values, both in terms of learning attitudes and the ability of learning outcomes. As for the supporting factors in the implementation of e-learning at MAN 1 Boalemo, most of them have been able to use e-learning media while the inhibiting factor is the limited internet quota for students. The solution to the inhibiting factor is that schools facilitate Internet and WIFI quotas for students.